2022
DOI: 10.1371/journal.pone.0270364
|View full text |Cite
|
Sign up to set email alerts
|

miR-1285-3p targets TPI1 to regulate the glycolysis metabolism signaling pathway of Tibetan sheep Sertoli cells

Abstract: Glycolysis in Sertoli cells (SCs) can provide energy substrates for the development of spermatogenic cells. Triose phosphate isomerase 1 (TPI1) is one of the key catalytic enzymes involved in glycolysis. However, the biological function of TPI1 in SCs and its role in glycolytic metabolic pathways are poorly understood. On the basis of a previous research, we isolated primary SCs from Tibetan sheep, and overexpressed TPI1 gene to determine its effect on the proliferation, glycolysis, and apoptosis of SCs. Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Most current research on miR-1285 concentrates on cancers, such as lung squamous cell carcinoma ( 35 ) and thyroid tumors ( 36 ). It has been found that TPI1, a pivotal enzyme in the glycolysis pathway, is a functional target of miR-1285-3p, and miR-1285-3p can diminish TPI1 expression in Sertoli cells ( 37 ). Another study established that inhibiting miR-122 safeguards hepatocytes from lipid metabolic disorders such as NAFLD and curbs lipogenesis by elevating Sirt1 and activating the AMPK pathway ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most current research on miR-1285 concentrates on cancers, such as lung squamous cell carcinoma ( 35 ) and thyroid tumors ( 36 ). It has been found that TPI1, a pivotal enzyme in the glycolysis pathway, is a functional target of miR-1285-3p, and miR-1285-3p can diminish TPI1 expression in Sertoli cells ( 37 ). Another study established that inhibiting miR-122 safeguards hepatocytes from lipid metabolic disorders such as NAFLD and curbs lipogenesis by elevating Sirt1 and activating the AMPK pathway ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified several potential regulatory miRNAs (miR-1285-z, miR-122-y, miR-150-x, and miR-130-x). The principal of miR-1285-3p, and can diminish TPI1 expression in Sertoli cells (37). Another study established that inhibiting miR-122 safeguards hepatocytes from lipid metabolic disorders such as NAFLD and curbs lipogenesis by elevating Sirt1 and activating the AMPK pathway (38).…”
Section: Discussionmentioning
confidence: 99%
“… 89 In addition, abnormalities in germ cell development at any stage can cause impaired spermatogenesis and ultimately lead to reduced fertility or infertility in mice. These studies found that Sertoli cells have an important role in spermatogenesis 90 , 91 and that alterations in cellular connections, cellular communication, and the microenvironment on which spermatogenesis depends can lead to abnormal germ cell development 92 and ultimately to fertility disorders. 93 These findings have provided ideas to address the infertility disorders of oligospermia and weak spermatozoa.…”
Section: The Role Of Exosomes Derived From Sertoli Cells In Testicula...mentioning
confidence: 99%